MARKETINING OF MILK BY DAIRY FARM PRODUCERS IN KHARTOUM STATE - Mohammed Tawfik Fawi, Nahid (Journal of Veterinary Medicine and Animal Production, 2022)
This research aimed at studying the marketing of milk by dairy farm producers in Khartoum state , Sudan. The importance of the research evolves from the importance of implementing modern marketing strategies in the conventional agricultural marketing especially the dairy sector. To achieve the objectives of the research, primary data was collected through distributing questionnaires to 60 dairy farm producers in Khartoum state, who had been selected by a stratified quota sampling procedure. After using descriptive statistical methods of analysis, some results were reached most important of which were; 1- Most of the producers set price according to supply and demand. 2- Producers pay great attention to the quality of the products to gain and retain the consumers.